Uji Organoleptis Masker Gel Peel-off Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius) dengan Variasi Konsentrasi Polivinil alcohol (PVA) - Daraini Mahdhalita; Ida Fauziah; Rahmiati Rahmiati; Sartini Sartini (Universitas Medan Area, 2023)
Pandan Wangi (Pandanus amaryllifolius) is a plant that grows in the tropics and is known to contain antioxidants. Pandan Wangi can be a garden plant or deliberately planted in the yard. The preparations made in this study were pandan extract peel-off gel masks with varying concentrations of polyvinyl alcohol (PVA). PVA is a water-soluble eco-friendly polymer. This study aims to determine the effect of PVA concentration on the physical quality of peel off gel mask preparations of fragrant pandan leaf extract. The research was conducted using laboratory experimental methods. Three gel peel off mask preparation formulas were used in the study, namely FI (5% PVA), FII (10% PVA) and FIII (15% PVA). Parameters for observing the quality of the peel off gel mask preparations included organoleptic tests, namely changes in aroma, color and shape as well as viscosity. The results showed that after a storage period of 28 days, the physical quality of the pandan leaf extract peel-off gel mask was still good. The mask preparation is characterized by a pale yellow color, smells of fragrant pandan extract and has a soft texture. Variation of PVA concentration affected the viscosity of the pandan leaf extract gel mask preparation.